Identifying Gaps in Prevention of Mother to Child Transmission of HIV: A Case Series of HIV-positive Infants in Zambia. Issue 7 (July 2016) - Bonawitz, Rachael; Sambambi, Kennedy; Vickery, Michelle; Hamomba, Leoda; Hammond, Emily; Duncan, Julie; Musokotwane, Kebby; Thea, Donald; Herlihy, Julie M.
Abstract : Background: To determine the timing of prevention of mother-to-child transmission cascade programmatic barriers to understand the service gaps in preparation for scale up of Option B+ in the Southern Province of Zambia. Methods: A database search of the National Dried Blood Spot Registry in Zambia for DNA polymerase chain reaction identified human immunodeficiency virus (HIV)-infected infants from 5 facilities in 2 districts in Southern Province, Zambia over a 6-month observation period (January 2013 to June 2013). Results: Seventeen HIV-positive infants out of 459 infants tested were identified from 5 health facilities that provided antiretroviral therapy (ART) initiation within the antenatal care (ANC) clinic, for a transmission rate of 3.7%. Possible risk factors identified for mother to child transmission of HIV included late ANC presentation, home delivery, provision of maternal short course prophylaxis, maternal refusal to initiate treatment and loss to follow-up. Conclusions: As Zambia transitions to life-long combination ART initiation for HIV-positive pregnant women under Option B+, and subsequent ART integration into ANC facilities, it is crucial to understand prevention of mother-to-child transmission program gaps to achieve the goal of eliminating mother to child transmission of HIV in Zambia.